Modeling porosity loss in Fe0-based permeable reactive barriers with Faraday’s law - Huichen Yang (Nature Portfolio, 2021)
Abstract Solid iron corrosion products (FeCPs), continuously generated from iron corrosion in Fe0-based permeable reactive barriers (PRB) at pH > 4.5, can lead to significant porosity loss and possibility of system’s failure. To avoid such failure and to estimate the long-term performance of PRBs, reliable models are required. In this study, a mathematical model is presented to describe the porosity change of a hypothetical Fe0-based PRB through-flowed by deionized water. The porosity loss is solely caused by iron corrosion process. The new model is based on Faraday’s Law and considers the iron surface passivation. Experimental results from literature were used to calibrate the parameters of the model. The derived iron corrosion rates (2.60 mmol/(kg day), 2.07 mmol/(kg day) and 1.77 mmol/(kg day)) are significantly larger than the corrosion rate used in previous modeling studies (0.4 mmol/(kg day)). This suggests that the previous models have underestimated the impact of in-situ generated FeCPs on the porosity loss. The model results show that the assumptions for the iron corrosion rates on basis of a first-order dependency on iron surface area are only valid when no iron surface passivation is considered. The simulations demonstrate that volume-expansion by Fe0 corrosion products alone can cause a great extent of porosity loss and suggests careful evaluation of the iron corrosion process in individual Fe0-based PRB.